Improvement and Accuracy Analysis of the Axis Fitting Method in Robot Kinematics Calibration - Huang Yuansong; Xi Wenming; Sun Jiandong (Jixie chuandong)
The central axis fitting accuracy of the axis rotation method determines the absolute positioning accuracy of the calibrated robot. In this study, two kinds of axis fitting methods are used, and their fitting accuracies are analyzed. The first kind is the traditional fitting method, which fits the measuring point as a circle and uses the normal vector through the center of the circle as the axis of the robot. The second kind is the improved fitting method, which uses the measuring point to fit the sphere and plane, and obtains the intersecting circle of the fitted sphere and plane. In order to avoid the large geometric parameter calibration error caused by the small error of the over-center normal vector in the traditional method, the line of the center of the double intersecting circle is used as the axis of the robot. Compared with the fitting results of the laser tracker software, the fitted center of the intersecting circle has higher accuracy. The axis vectors of the first and the second axes are used, the axis vector of the first axis and the projection of the axis vector of the second axis on the vertical plane of the first axis are respectively used as the direction vector of the robot base coordinate system, and the conversion matrix of the measurement point from the measurement system to the robot system is constructed. By comparing the measurement point difference after conversion of the two conversion matrices, the conversion matrix using the second axis directly as the base coordinate system direction vector has a large measurement point conversion error.